The lactylation-macrophage interplay: implications for gastrointestinal disease therapeutics - Che, Xinzhen; Zhang, Yixin; Chen, Xiqi; Xie, Guangdong; Li, Jinling; Xu, Chengchao; Zhang, Chunhua; Zhu, Yong; Yang, Xinyu (Frontiers in Immunology, 2025)
Lactate, a key metabolic byproduct of the Warburg effect, has lately been recognized as a regulator of histone lysine lactylation, a unique post-translational modification that plays a crucial role in essential biological processes, including the regulation of gene transcription. Lactylation plays a crucial regulatory role in macrophage biology by influencing inflammatory responses, tumor immune evasion, and fibrotic development. This review methodically investigates the molecular mechanisms of lactate metabolism and lactylation modification, focusing on their roles in macrophage activation and polarization in relation to gastrointestinal disorders, such as gastric cancer, colorectal carcinoma, ulcerative colitis, postoperative ileus, and bacterial and viral gastrointestinal infections. We clarify the molecular switching role of lactylation in regulating macrophage polarization under pathological settings by integrating current developments in epigenetic regulation and metabolic reprogramming. Current evidence demonstrates the dual regulatory role of lactylation in macrophage-mediated immune responses: it fosters anti-inflammatory and reparative phenotypes, yet may paradoxically expedite tumor progression and induce immunosuppressive conditions in certain gastrointestinal microenvironments. This review emphasizes that exploring lactylation as a novel therapeutic target offers new insights into gastrointestinal pathogenesis and lays a molecular groundwork for formulating precision therapeutic strategies against inflammatory diseases and malignant tumors.